Knowledge, attitudes, and preferences regarding End-of-Life Care among older adults in a tertiary care centre, Northern Sri Lanka - Pradeepan, J.; Kumanan, T.; Suganthan, N.; Selvaratnam, G.; Sujanitha, V.; Brammah, R.; Balendran, K.; Pathmanathan, D.; Rubakumar, D.; Mohanathas, S. (University Medical Unit, Teaching Hospital, Jaffna, Sri Lanka, Department of Medicine, Faculty of Medicine, University of Jaffna, Sri Lanka, 2025)
Introduction:End-of-life (EOL) care is a vital component of healthcare that emphasises comfort, dignity, and quality of life during the terminal stages of illness. Although its significance is widely recognised, awareness and understanding of EOL care remain limited in many low- and middle-income countries, including Sri Lanka. Improving knowledge and aligning care with patient preferences can help clinicians deliver patient-centred, culturally sensitive, and cost-effective interventions and inform policy development for EOL care frameworks. Objective: This study aimed to assess the knowledge, attitudes, and preferences regarding EOL care among older adults attending the medical outpatient department at the Teaching Hospital Jaffna, and to facilitate patient-centred, costeffective care planning. Methods: A descriptive cross-sectional study was conducted between November 2024 and January 2025 involving 510 patients aged 65 years and above. Data were collected using a pre-validated, self-administered questionnaire. Statistical analysis was performed using SPSS version 27 Results: The majority of participants were female (65.7%), with the largest proportion aged 70-79 years (56.3%). In terms of education, 80% of patients had formal education. Multimorbidity was prevalent, with 84.9% reporting three or more chronic conditions, notably hypertension (72.9%), diabetes mellitus (54.7%), and dyslipidaemia (51.2%). A large majority (90%) lived with family, suggesting strong family support. While 77.3% acknowledged the irreversible nature of chronic disease and 97% preferred comfort-focused management at terminal stages, only 23.5% were aware of palliative or EOL care concepts. Paradoxically, 71.6% desired continuation of treatment even if futile, and 86% favoured resuscitation and intensive care during terminal illness. Clear communication on disease progression was valued by 76.5%. Decision-making responsibility was seen as shared among patients (34%), families (34%), and physicians (32%). Most respondents (86.3%) found EOL care meaningful, and 89.2% were open to discussing EOL care with healthcare providers. Conclusion: Elderly patients with multimorbidity attending a tertiary care unit in the Northern region of Sri Lanka value communication and recognize the importance of EOL care but show limited awareness and mixed preferences, often favouring active medical interventions despite a desire for comfort. Better patient education and culturally sensitive dialogue are necessary to align EOL decisions with patient values and cultural context.